Embedded photographic tomography - Fong-On, Chutima; Visitsattapongse, Sarinporn; Pintavirooj, C. (My University, 2018)
Tomographic imaging is a technique for reconnaissance of a cross-section of an inspected object without destruction and taken at a prior-known angle. Input data that were known as the projection are gathered by repeatedly capturing image through the object in a number of viewpoints. In this paper, we designed the embedded photographic tomography that can be used for a basic purpose. A number of digital cameras are attached on the rotating to capture a series of images around the object. This mimics a cone-beam projection. Here, its application is focused on the 3D modeling. In order to design the embedded system, Raspberry Pi is used as the main microcontroller that use for digital image processing in acquisition system. The Processing system will use projection data for reconstruction and 3D modeling process.
Keywords: 3D Rendering; Image Reconstruction; Photographic Tomography